Discovery of RNA secondary structural motifs using sequence-ordered thermodynamic stability and comparative sequence analysis - Jake M. Peterson; Collin A. O'Leary; Evelyn C. Coppenbarger; Van S. Tompkins; Walter N. Moss (MethodsX, 2023)
Major advances in RNA secondary structural motif prediction have been achieved in the last few years; however, few methods harness the predictive power of multiple approaches to deliver in-depth characterizations of local RNA motifs and their potential functionality. Additionally, most available methods do not predict RNA pseudoknots. This work combines complementary bioinformatic systems into one robust discovery pipeline where: • RNA sequences are folded to search for thermodynamically favorable motifs utilizing ScanFold. • Motifs are expanded and refolded into alternate pseudoknot conformations by Knotty/Iterative HFold. • All conformations are evaluated for covariance via the cm-builder pipeline (Infernal and R-scape).